Startup Myths and Models : What You Won't Learn in Business School - Virk, Rizwan (Columbia University Press, 2020)
Budding entrepreneurs face a challenging road. The path is not made any easier by all the clichés they hear about how to make a startup succeed-from platitudes and conventional wisdom to downright contradictions.This witty and wise guide to the dilemmas of entrepreneurship debunks widespread misconceptions about how the world of startups works and offers hard-earned advice for every step of the journey. Instead of startup myths-legends spun from a fantasy version of Silicon Valley-Rizwan Virk provides startup models-frameworks that help make thoughtful decisions about starting, growing, managing, and selling a business. Rather than dispensing simplistic rules, he mentors readers in the development of a mental toolkit for approaching challenges based on how startup markets evolve in real life.In snappy prose with savvy pop-culture and real-world examples, Virk recasts entrepreneurship as a grand adventure. He points out the pitfalls that appear along the way and offers insights into how to avoid them, sharing the secrets of founding a startup, raising money, hiring and firing, when to enter a market and when to exit, and how to value a company.Virk combines lessons learned the hard way during his twenty-five years of founding, investing in, and advising startups with reflections from well-known venture capitalists and experts. His candid advice makes Startup Myths and Models an ideal guide for those readers just embarking on the startup life and those looking for their next adventure.